Compact 3D Metal Collectors Enabled by Roll‐to‐Roll Nanoimprinting for Improving Capacitive Energy Storage (Small Methods 4/2022). Issue 4 (18th April 2022) - Zheng, Qinwen; Li, Xiangming; Yang, Qingzhen; Li, Congming; Wu, Lifeng; Wang, Yingche; Sun, Pengcheng; Tian, Hongmiao; Wang, Chunhui; Chen, Xiaoliang; Shao, Jinyou
Abstract : Front Cover In article number 2101539, Xiangming Li, Jinyou Shao, and co‐workers demonstrate a roll‐to‐roll nanoimprinting method to deform flat aluminum foils into 3D current collectors with hierarchical microstructures. The 3D current collector significantly reduces the contact resistance by an order of magnitude, which comprehensively improves the electrochemical performance of the supercapacitor. The method can be extended to other systems that involve microstructured metal interfaces, such as batteries.